Evaluasi Penerapan Penilaian Tingkat Maturitas BLU pada Perguruan Tinggi - Mandisa, Ayub; Martani, Dwi (Jurnal Manajemen Bisnis dan Keuangan, 2023)
BLU maturity rating assessment is an assessment method for assessing the performance of Public Service Agencies (BLU) which operate in several fields and have different characteristics. This study aims to assess the maturity level assessment method of BLU as a method for assessing BLU performance in the education sector. This study uses a qualitative descriptive analysis method. The results of the study show that the maturity level of BLU, in general, is in accordance with other performance assessment methods, such as the assessment of the soundness level of BUMN and accredited BAN-PT accreditation. Even so, there are adjustments that must be made, namely by differentiating aspects of the assessment based on the type of service and the size of a BLU.